Antimicrobial Activity of Aspergillus sp. from the Amazon Biome: Isolation of Kojic Acid - Rodrigues, Josy Caldas; Lima da Silva, Weison; Ribeiro da Silva, David; Maia, Carolina Rabelo; Santos Goiabeira, Clarice Virginia; Figueiredo Chagas, Haile Dean; Ayres D’Elia, Gigliola Mayara; Barbosa Alves, Gleica Soyan; Zahner, Viviane; Nunez, Cecilia Veronica; Cristo Fernandes, Ormezinda Celeste (International Journal of Microbiology, 2022)
The antimicrobial potential of Aspergillus sp., isolated from the Amazon biome, which is stored at the Amazon Fungi Collection-CFAM at ILMD/FIOCRUZ, was evaluated. The fungal culture was cultivated in yeast extract agar and sucrose (YES) for cold extraction of the biocompounds in ethyl acetate at 28 °C for 7 days in a BOD type incubator. The obtained extract was evaluated for its antimicrobial activity against Candida albicans and Gram-positive and negative bacteria by the “cup plate” method and the determination of the minimum inhibitory concentration (MIC) by the broth microdilution method. The extract was subjected to thin layer chromatography (TLC) and fractionated by open and semipreparative column chromatography. The fractions of interest had their chemical constituents elucidated by nuclear magnetic resonance and mass spectrometry. The elucidated molecule was evaluated for cytotoxicity against the human fibroblast strain (MRC5). The extract presented inhibitory activity against both Gram-positive and negative bacteria, with the range of inhibition halos from 5.3 to 14 mm in diameter and an MIC ranging from 500 to 15.6 μg/mL. Seventy-one fractions were collected and TLC analysis suggested the presence of substances with double bond groups: coumarins, flavonoids, phenolic, alkaloids, and terpenes. NMR and MS analyses demonstrated that the isolated molecule was kojic acid. The results of the cytotoxicity test showed that MRC5 cells presented viability at concentrations from 500 to 7.81 μg/mL. The kojic acid molecule of Aspergillus sp., with antibacterial activity and moderate toxicity at the concentrations tested, is a promising prototype of an alternative active principle of an antimicrobial drug.